Comportamentos sexuais na infância : uma comparação entre grupos de crianças com vivência de abusos sexuais, maus-tratos e problemas de comportamento - Miele, Adriana (2015)
The manifestation of sexual behavior in childhood is expected and present in typical child development. However, disorders involving sexual behavior are often related to cases of sexual abuse. The variable sexual behavior is therefore taken into account in most psychological assessments aimed at diagnosing situations and abusive sexual experiences. For the inclusion of the assessment of these behaviors in an objective and reliable sexual victimization diagnostic procedure, the use of adequate evaluation tools for the child's cultural context is required. This study inquires about the sexual behavior of children between six and twelve years and compares the differences in the frequency and intensity of these behaviors from children of three different groups: victims of sexual abuse, victims of abuse and with clinical symptoms. The empirical section investigates the differences in the occurrence of sexual behavior between groups and the influence of social-demographic variables. In order to accomplish this, the translation and adaptation of the Child Sexual Behavior Inventory (CSBI) (Friedrich, 1997) was held, which served as a tool to survey the type, intensity and frequency of sexual behaviors in the studied sample. No significant differences were found between the groups in the total score of CSBI. However, the instrument's domain responsible for investigating sexual knowledge inappropriate for the child's age was different between groups, with the group who experienced sexual abuse presenting significantly more behaviors related to that domain. Besides the empirical section, a theoretical study, focused upon academic works that have addressed the issue of sexual behaviors in childhood and its relation to the experience of sexual abuse, was developed. The studies that made up the review were published between the years 2003 and 2013. Eight studies, from five different countries, were selected. Most instruments used in these studies were the CSBI and the CBCL. There were no studies in the national context that addressed the issue of sexual behaviors. Noteworthy is also the small number of works addressing the selected theme.